2014
DOI: 10.1007/s00701-014-2190-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction after retrosigmoid approaches using autologous fat graft-assisted Medpor Titan cranioplasty: assessment of postoperative cerebrospinal fluid leaks and headaches in 60 cases

Abstract: Our multilayer repair technique with a fat graft-assisted Medpor Titan cranioplasty appears effective in preventing postoperative CSF leaks and new-onset postoperative headaches after retrosigmoid approaches. Postoperative lumbar drainage may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…Additionally, a multilayered soft tissue closure may also be an important factor in reducing the risk of postoperative headaches, since the posterior fossa dura and suboccipital muscles are rich in blood supply and innervation. 11,15 In our series, 2 of 25 patients (8%) reported persistent postoperative headaches during the mean follow-up period of 16 months, with an average severity of 6/10 on the visual analog scale. This is consistent with previous reports (►Table 1) and suggests that a repair technique that reestablishes anatomic separation between the dura and extracranial soft tissues may be an important factor.…”
Section: Headachesmentioning
confidence: 60%
See 2 more Smart Citations
“…Additionally, a multilayered soft tissue closure may also be an important factor in reducing the risk of postoperative headaches, since the posterior fossa dura and suboccipital muscles are rich in blood supply and innervation. 11,15 In our series, 2 of 25 patients (8%) reported persistent postoperative headaches during the mean follow-up period of 16 months, with an average severity of 6/10 on the visual analog scale. This is consistent with previous reports (►Table 1) and suggests that a repair technique that reestablishes anatomic separation between the dura and extracranial soft tissues may be an important factor.…”
Section: Headachesmentioning
confidence: 60%
“…[4][5][6][7]9 Prevention of CSF leak is extremely important, as it increases the risk of meningitis and often requires additional procedures such as percutaneous drainage of pseudomeningoceles, lumbar drain insertion, and surgical reexploration. 11,12 To address this complication, many authors have described reconstruction techniques that focus on achieving a watertight dural closure. For example, Samii et al reported a 2% incidence of CSF leak in a series of 200 patients closed with primary dural closure along with a pericranial flap.…”
Section: Cranial Reconstruction Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The cranioplasty for bone defects is also crucial for preventing CSF leaks. As mentioned above, the CSF leakage was significantly lower in the group that filled bone defects using bone cement than titanium mesh [7,[16][17][18]. However, fat graft-assisted titanium cranioplasty could also prevent postoperative CSF leak [17].…”
Section: Discussionmentioning
confidence: 87%
“…As mentioned above, the CSF leakage was significantly lower in the group that filled bone defects using bone cement than titanium mesh [7,[16][17][18]. However, fat graft-assisted titanium cranioplasty could also prevent postoperative CSF leak [17]. While the rigid titanium mesh maintains its contour after closing the scalp, the dead space between the dura suture site and mesh may also cause a driving force of negative pressure to make CSF leak at the dural closure site.…”
Section: Discussionmentioning
confidence: 95%